Very Late Local Relapse of Ewing's Sarcoma of the Head and Neck treated with Aggressive Multimodal Therapy. (20th May 2008) - Thariat, J.; Italiano, A.; Peyrade, F.; Birtwisle-Peyrottes, I.; Gastaud, L.; Dassonville, O.; Thyss, A.
Abstract : Ewing's sarcoma's relapse rarely occurs more than two years after the initial diagnosis. We report the case of a 26-year-old man with a history of Ewing's sarcoma of the left maxillary sinus at the age of 10 who presented with a very late local relapse, 16 years after the first occurrence of disease. Ultimate control was achieved after multimodal therapy including surgery, high-dose chemotherapy, and radiotherapy. This report indicates that local relapses of Ewing's sarcoma can be treated with curative intent in selected cases.